Would depositors like to show others that they do not withdraw? Theory and experiment - Markus Kinateder; Hubert János Kiss; Ágnes Pintér (Hungarian Academy of Sciences, Institute of Economics, 2015)
There is an asymmetry regarding what previous decisions depositors may observe when choosing whether to withdraw or keep the money deposited: it is more likely that withdrawals are observed. We study how decision-making changes if depositors are able to make their decision to keep their funds in the bank visible to subsequent depositors at a cost. We show theoretically in a Diamond-Dybvig setup that without this signaling option multiple equilibria are possible, while signaling makes the no-run outcome the unique equilibrium. We test if the theoretical predicitions hold in a lab experiment. We find that indeed when signaling is available, bank runs are less likely to arise and signaling is extensively used.
Keywords: C72; C91; D80; G21; 330; Bank runs; Asymmetric information; Experimental evidence; Signaling